Application of plasma metagenomic next-generation sequencing improves prognosis in hematology patients with neutropenia or hematopoietic stem cell transplantation for infection - Chen, Yuhui; Wang, Jinjin; Gan, Xinai; Li, Meng; Liao, Yi; Zhou, Yongzhao; Niu, Ting (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Metagenomic next-generation sequencing (mNGS) is a novel technique for detecting pathogens. This retrospective study evaluated the diagnostic value of mNGS using plasma for infections in hematology patients and its impact on clinical treatment and prognosis in different subgroups of hematology patients. Methods A total of 153 hematology patients with suspected infection who underwent mNGS using plasma were enrolled in the study. Their clinical histories, conventional microbiological test (CMT) results, mNGS results, treatment and prognosis were retrospectively analyzed. Results In 153 plasma samples, mNGS yielded a higher positivity rate than CMT (total: 88.24% vs. 40.52%, P<0.001; bacteria: 35.95% vs. 21.57%, P < 0.01; virus: 69.93% vs. 21.57%, P<0.001; fungi: 20.26% vs. 7.84%, P<0.01). mNGS had a higher positivity rate for bacteria and fungi in the neutropenia group than in the non-neutropenia group (bacteria: 48.61% vs. 24.69%, P<0.01; fungi: 27.78% vs. 13.58%, P<0.05). mNGS demonstrated a greater advantage in the group of patients with hematopoietic stem cell transplantation (HSCT). Both the 3-day and 7-day efficacy rates in the HSCT group were higher than those in the non-HSCT group (3-day: 82.22% vs. 58.65%, P < 0.01; 7-day: 88.89% vs. 67.31%, P < 0.01), and the 28-day mortality rate was lower in the HSCT group than in the non-HSCT group (6.67% vs. 38.89%, P < 0.000). The neutropenia group achieved similar efficacy and mortality rates to the non-neutropenia group (7-day efficiency rate: 76.39% vs. 71.43%, P > 0.05; mortality rate: 29.17% vs. 29.63%, P > 0.05) with more aggressive antibiotic adjustments (45.83% vs. 22.22%, P < 0.01). Conclusion mNGS can detect more microorganisms with higher positive rates, especially in patients with neutropenia. mNGS had better clinical value in patients with hematopoietic stem cell transplantation (HSCT) or neutropenia, which had a positive effect on treatment and prognosis.